VISIONARY LEADERSHIP IMPLEMENTATION OF STRATEGIC VALUES IN BUILDING THE REPUTATION OF EDUCATIONAL INSTITUTIONS - Evi Susi Sandrawita br. Saragih; Anis Widayati; Sandra Dewi; Herlina; Widyatmike; Akhmad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the role of visionary leadership in implementing strategic values to build the reputation of educational institutions. Visionary leadership is considered a key factor in directing the school’s vision and mission, fostering a collaborative culture, and optimizing available resources. Using a qualitative descriptive approach, this research highlights how educational leaders embed values of innovation, accountability, transparency, and sustainability into school management practices. The findings indicate that visionary leadership not only enhances the quality of educational services but also strengthens public trust and institutional competitiveness. Therefore, visionary leadership serves as a strategic foundation for building a sustainable reputation of educational institutions in the era of globalization.